Edukasi PPh Badan Dengan Coretax Bagi Pelaku UMKM Desa Sarireja Kecamatan Jalancagak Kabupaten Subang - Saepul Bahri; Teguh Djatmiko; Siska Rahmayanti; Meida Fitriani (ADINDAMAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
The digital transformation of tax administration through the Core Tax Administration System (Coretax) requires Micro, Small, and Medium Enterprises (MSMEs) to possess adequate tax literacy and digital skills. However, observations by the Community Service (PKM) team in Sarireja Village, Jalancagak Subdistrict, Subang Regency, indicate that the majority of MSME operators do not yet understand the provisions of Corporate Income Tax (PPh), are unfamiliar with Coretax, and still face difficulties with digital-based tax administration. This PKM initiative aims to enhance MSME operators’ knowledge, skills, and awareness regarding Corporate Income Tax (PPh Badan) as well as their ability to independently operate Coretax. The implementation method employs a Participatory Action Learning (PAL) approach comprising five stages: needs assessment, preparation, education and training, mentoring, and evaluation through pre- and post-tests for 33 participants. Educational activities were conducted through interactive lectures, demonstrations, hands-on practice using Coretax, discussions, and individual consultations. The results of the program showed a significant improvement in participants’ level of understanding, as evidenced by an increase in the average pre-test score from 34.52 to 80.24 on the post-test—a rise of 45.72 points (132.48%). In addition, the majority of participants were able to understand the concept of corporate income tax, perform tax administration simulations, and operate Coretax’s basic features independently. Thus, this Community Service Program (PKM) successfully improved the tax literacy and digital competencies of MSME actors, thereby supporting increased tax compliance, strengthening business administrative governance, accelerating adaptation to digital tax transformation, and supporting the success of tax administration reform in Indonesia.